Mediterranean diet effects on ventricular premature complexes (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate the relationship between ventricular premature complexes (VPC) and Mediterranean diet score. Rhythm disturbances in the heart significantly affect the quality of life of the patients. Material and Methods: This study was conducted on 50 patients with palpitations who were referred to the cardiology outpatient clinic and had more than 10000 VPC per day as a result of a 24-hour holter, and 50 patients who presented with palpitations but had less than 10,000 VPC in the holter. Diet quality was determined by scoring method (5, 6-9 and ≥10 points) ‘Mediterranean Diet Adaptation Scale’ and compared between groups.Results: There was no difference between the two groups in terms of clinical and demographic characteristics. Mediterranean diet scores were found lower in patients with VPC’s ≥10.000/day (p0.001). There was a significant negative correlation found between number of VPC and Mediterranean diet score (p0.001, r = -0.652).Conclusion: The protective role of Mediterranean diet type nutrition on the frequency of VPC was clearly observed in our study. This study, which is one of the limited numbers of studies examining the relationship between Mediterranean diet and VPC, may be helpful in understanding the pathophysiology of VPC.
Keywords: Ventricular premature complexes; Mediterranean diet score; arrhythmia